Review of Clinical Ethics Consultation - A Practical Guide - Gill, Julia (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
In this guide to conducting clinical ethics consultation, Bashir Jiwani notes that the success of ethics interventions often relies on the personal skills of the particular consultant involved. Therefore, he wrote this volume to articulate the elements of clinical ethics consultation to help foster integrity in those who may not have these inherent skills. By focusing on fostering integrity, this book provides a fresh perspective and process for how to approach clinical ethics consultation without necessarily having to rely on the teaching of others or the advice to simply do what we have seen mentors do.